2000
DOI: 10.1345/aph.19310
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Clinical Interventions by Pharmacy Faculty, Residents, and Students

Abstract: This study demonstrates that educational activities by pharmacy faculty, residents, and students have a positive influence on patient care in a community hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 2 publications
1
56
0
Order By: Relevance
“…Previously documented acceptance rates for pharmacy students' verbal and written recommendations range from 64% and 95%. [2][3][4][5][6][7]10 Verbal recommendations may have a higher rate of acceptance due to student's face-to-face time with the resident physician and the opportunity to engage in discussions regarding patient-specific recommendations. Although the resident physicians in this study were trained to look for the pharmacotherapy notes in the medical record, the possibility exists that the students' written recommendations were overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously documented acceptance rates for pharmacy students' verbal and written recommendations range from 64% and 95%. [2][3][4][5][6][7]10 Verbal recommendations may have a higher rate of acceptance due to student's face-to-face time with the resident physician and the opportunity to engage in discussions regarding patient-specific recommendations. Although the resident physicians in this study were trained to look for the pharmacotherapy notes in the medical record, the possibility exists that the students' written recommendations were overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Interventions in an outpatient ambulatory care clinic made by a clinical pharmacist not only improved patient care, but also yielded a cost savings 4 times the pharmacist salary when compared to a similar clinic without a pharmacist. 8,9 To date, there have been no studies that compared pharmacy students' written versus verbal recommendations in an ambulatory clinic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Current literature regarding student pharmacist documentation of interventions is limited to small studies that report results from single clinical sites rather than across a class or school. 6,13,14,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In addition, even fewer publications describe documentation of clinical pharmacy interventions made by pharmacy residents. 13,14,31,44 Only one published study focused on school-wide documentation of clinical interventions by student pharmacists and faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…The overall estimated cost avoidance resulting from the interventions by faculty members, residents and students was $172,655. 31 Lee and colleagues found that student pharmacists' interventions along with interventions by 36 staff pharmacists and 5 pharmacy residents resulted in cost savings and cost avoidance in a veterans medical center. 6 The authors' recorded 600 interventions within the medical center over a 1-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have described the types of clinical services provided by pharmacy students during experiential courses. [2][3][4][5][6][7] However, the impact of these student interventions is limited in terms of objectively measured patient outcomes. Therefore, members of the primary care faculty division from Texas Tech Health Sciences Center (TTUHSC) School of Pharmacy developed a project to evaluate the effect of precepted student participation in ambulatory care clinics on the percentage of therapeutic INR results among patients on chronic warfarin therapy.…”
Section: Introductionmentioning
confidence: 99%